Infrapopliteal Bypass In Patients On Dialysis: Patency And Survival - Duarte, Armanda (2024)
Introduction Portugal has one of the highest prevalence of patients on a regular dialysis program. This population has a higher incidence of peripheral arterial disease with higher rates of postoperative morbidity and mortality. Our goal was to compare outcomes between dialysis and non-dialysis patients with chronic limb threatening ischemia (CLTI) submitted to infrapopliteal bypass. Materials and Methods A retrospective single-center study of infrapopliteal bypass for CLTI was performed between 2012 and 2019. Patients were divided in two groups based on dialysis status (group 1 incorporated patients on dialysis). Primary end point was 1-year freedom from CLTI. Secondary end points were limb-salvage, survival and primary (PP) and tertiary patency (TP) rates at 3 years of follow-up. Results A total of 352 infrapopliteal bypasses were performed in 310 patients with CLTI. Fourteen percent of the revascularizations were performed on dialysis patients (48/352). Median age was 73 years (interquartile range - IQR 15) and 74% (259/352) were male. Median follow-up was 26 months (IQR 42). Overall, 92% (325/352) had tissue loss and 44% (154/352) had some degree of infection. The majority of revascularization procedures were performed with vein grafts (61%, 214/352). The 30-day mortality was 4% (11/310), with no difference between groups (p = 0.627). Kaplan-Meier analysis showed no difference between groups regarding freedom from CLTI (76% vs. 79%; HR 0.96, CI 0.65–1.44, p=0.857), limb-salvage (70% vs. 82%; HR 1.40, CI 0.71–2.78, p=0.327) and survival (62% vs. 64%; HR 1.08, CI 0.60–1.94, p=0.799). PP rates were 39% in group 1 and 64% in group 2 (HR 1.71, CI 1.05–2.79, p=0.030). TP rates were not different between groups (57% and 78%; HR 1.79, CI 0.92–3.47, p=0.082). Conclusion Infrapopliteal bypass for CLTI, on dialysis patients, resulted in lower PP rates. No differences were observed in freedom from CLTI, TP, limb salvage and survival.